Correlation analysis between biomechanical characteristics of lower extremities during front roundhouse kick in Taekwondo and effective scores of electronic protectors - Jia, Mengyao; Ma, Yong; Huang, Ruifeng; Liu, Lin; Wang, Zhaoyi; Lin, Shijie; Peng, Qian; Xiong, Jun; Zheng, Weitao (Frontiers in Bioengineering and Biotechnology, 2024)
Objective The purpose of this study is to analyze the inherent relationship between the score values and the biomechanical characteristics of the forward kicking motion, we aim to identify the fundamental variables influencing the score values of the forward kicking motion and establish the key biomechanical factors that effectively trigger scoring in the forward kicking motion. Methods: The DaeDo electronic scoring system was used with the Vicon optical motion capture system and the Kistler 3D force platform to obtain kinematic and kinetic variables of the front roundhouse kick motion. Linear bivariate correlation analysis and principal component analysis were used to analyze the associations between kinematic, kinetic variables, and scoring values, and summarize key biomechanical factors for effectively scoring. Results The peak ankle plantar flexion angle and knee extension torque of the kicking leg showed a significant negative correlation with scoring values (r<0, p<0.05), while other variables showed no statistical significance. The peak knee flexion angle and hip extension angular velocity of the supporting leg showed a significant positive correlation with scoring values (r>0, p<0.01), while the peak ankle plantar flexion torque showed a significant negative correlation with scoring values (r<0, p<0.05), and other variables showed no statistically significant correlation. The absolute values of eigenvectors of the first and second principal components, which included hip angular velocity, ankle angle, knee torque, and hip torque, were relatively large, indicating their strong influence on effective scoring triggering. Conclusion Maintaining ankle dorsiflexion and a larger knee flexion angle in the kicking leg is favorable for triggering scoring. Higher knee flexion angle and hip extension angular velocity in the supporting leg are also advantageous for triggering scoring. "Body posture" and "Strength" are key factors that effectively trigger scoring.